2020
DOI: 10.3389/fgene.2020.00724
|View full text |Cite
|
Sign up to set email alerts
|

Catechol-O-methyltransferase Val158Met Genotype and Early-Life Family Adversity Interactively Affect Attention-Deficit Hyperactivity Symptoms Across Childhood

Abstract: Attention-deficit hyperactivity disorder (ADHD) is among the most commonly diagnosed psychiatric disorders of childhood. The dopaminergic system has been shown to have substantial effects on its etiology, with both functional Catechol- O -methyltransferase ( COMT ) Val 158 Met genotype and early-life environmental adversity involved in the risk of inattention and hyperactivity/impulsivity symptoms. In this prospecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 93 publications
(104 reference statements)
0
12
0
Order By: Relevance
“…The gene-environment interaction has also been studied by Nobile et al [41], where they demonstrated that adolescents with the Val/Val genotype and low SES exhibit significantly higher scores on attention deficit/hyperactivity problems. On the other hand, a recent study by Abraham et al [60] demonstrated that both boys and girls with at least one copy of the Met allele were more susceptible to being affected by early life adversities and express hyperactivity and impulsivity symptoms [60]. In both studies, Val158Met did not have a significant main effect on the hyperactivity and impulsivity scores.…”
Section: Environmental Factorsmentioning
confidence: 88%
See 4 more Smart Citations
“…The gene-environment interaction has also been studied by Nobile et al [41], where they demonstrated that adolescents with the Val/Val genotype and low SES exhibit significantly higher scores on attention deficit/hyperactivity problems. On the other hand, a recent study by Abraham et al [60] demonstrated that both boys and girls with at least one copy of the Met allele were more susceptible to being affected by early life adversities and express hyperactivity and impulsivity symptoms [60]. In both studies, Val158Met did not have a significant main effect on the hyperactivity and impulsivity scores.…”
Section: Environmental Factorsmentioning
confidence: 88%
“…Ethnicity may also influence the association between Val158Met and psychopathic traits in youth, where African American participants show an increased chance of having the Val/Val genotype when compared with White participants [60]. Another study with a sample composed of 88% European Caucasian, and 22% African Canadian and mixed ancestry participants, only the European subgroup showed a significant association between Val158Met and CU scores, when the whole population did not [54].…”
Section: Other Factors Ethnicitymentioning
confidence: 97%
See 3 more Smart Citations